Pengaruh Lokasi dan Citra Sekolah Terhadap Keputusan Siswa Memilih Sekolah di Sekolah Menengah Atas Negeri - Achmad Krisbiyanto; Ismatun Nadhifah (Academicus: Journal of Teaching and Learning, 2022)
This article aims to determine the effect of school location and image on students' decisions to choose schools. With a strategic location and a good school image, it will attract students' interest, so it has an impact on students' decisions in choosing a school. This article uses the independent variables of school location and image and the dependent variable of decision making. The population in this study were students of SMAN 1 Gondang Mojokerto. In this study, the sampling technique used by the researcher is probability sampling, which uses simple random sampling. Collecting data using a questionnaire distributed to respondents as many as 277 students. The results of this study indicate that the location and image of the school have a positive and significant effect on students' decisions to choose a school simultaneously, as seen from the results of the F test F-count of 6.235 > F-table of 3.028 and a significance value of 0.002 <0.05, but partially the location variable has no effect on decisions. students choose schools seen from the results of the T-test -0.207 < t table of 1.967. While the school image variable has a positive and significant effect on students' decisions to choose a school, as seen from the results of the T test of 3,527 > t table of 1,967.